Analisis Perilaku “CERDIK PTM” dengan Pendekatan Theory of Planned Behavior untuk Pencegahan Hipertensi pada Remaja di Kota Jayapura - Adimuntja, Natalia Paskawati; Nabuasa, Christin Debora; Asriati, Asriati; Pamangin, Lisda Oktavia Madu; Nurdin, Muhammad Akbar; Maturbongs, Margaretha Rosari (Jurnal Kesehatan Komunitas, 2025)
The prevalence of hypertension in Jayapura City is 35.03% (1). Implementation of CERDIK PTM behavior for adolescents is important to improve health status, efforts to improve clean and healthy living behavior, monitoring and early detection of NCD risk factors. This study aimed to determine the factors related to the behavior of "CERDIK PTM" for adolescent hypertension prevention with the theory of planned behavior approach in Jayapura City. This type of research is a cross-sectional survey. The study population was adolescents aged 15-19 years with a sample size of 343 respondents. The sampling technique used was cluster random sampling with univariate and bivariate analysis. The results of this study found that adolescents with "CERDIK PTM" behavior for hypertension prevention were in the poor category of 50.7% and adolescents with "CERDIK PTM" behavior for hypertension prevention were in the good category of 49.3%. The results of the bivariate analysis showed a relationship between attitudes (p-value = 0.000; RP = 0.65), subjective norms (p-value = 0.001; RP = 0.68), and perceived behavioral control (p-value = 0.001; RP = 1.42) with the behavior of "CERDIK PTM" for adolescent hypertension prevention in Jayapura City. The conclusion is that there is a relationship between attitudes, subjective norms, and perceived behavioral control with the behavior of "CERDIK PTM" for adolescents hypertension prevention in Jayapura City. Suggestions for educational institutions can coordinate with the community health center to carry out routine blood pressure checks.